Pengaruh Profitabilitas Perusahaan Terhadap Return Saham pada Perusahaan Dalam Indeks Lq45 - Budidarma, I Gusti Agung Musa (JBE (Journal of Business and Economics); Volume 10 No.1, 2011 JBE UNKLAB, 2011)
This paper seeks to find out whether Operating Profit Margin (OPM), Net Profit Margin (NPM), Earnings Per Share (EPS), Return On Total Assets (ROA), and Return On Equity (ROE)  influence the stock return of LQ45 index firms. The sample consists of 13 firms over the period 2008 to 2010. The study uses simple regression analysis with stock return as dependent variable with OPM,NPM,EPS,ROA, and ROE as independent variables. Result of test indicates that only EPS having an influence to stock return.